Effectiveness of reinforcement on soil subsidence - Tulebekova, A.; Tanyrbergenova, G.; Zhankina, A.; Baizakova, G. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2023)
The application of methods of improvement of ground bases in subsidence areas is an urgent issue today. This is evidenced by the continuing difficulties with the operation of transport structures. This study presents experimental studies of soil reinforcement. An important factor is to determine the properties of the soil, so the paper presents the results of laboratory tests. The angle of internal friction and the deformation increases to a greater extent when the reinforcing element is embedded in the ground, which will increase the bearing capacity of the foundations and reduce the deformability and settlement of the soil mass. The use of a reinforcing element in the ground not only makes it possible to improve the physical and mechanical properties of the soil but also gives an economic effect. It allows you to reduce the cost of the volume of earthworks. The results obtained in this study have considerable potential for eliminating problems arising from the construction of structures in subsidence areas.